Implementation of Health Action Process Approach to Improve Dietary Adherence in Type 2 Diabetic Patient - Kusnanto Kusnanto; Iqlima Dwi Kurnia; Dwi Indah Prasetia (Universitas Airlangga, 2015)
Introduction:Type 2 diabetic patients usually unsuccessful to follow the diet recommendation due to lack of motivation, memory and intention. This study attempts to increase the motivation and also to improve intention in dietary adherence through the implementation of Health Action Process Approach (HAPA).Method: This study was a quasy-experiment. The population were type 2 diabetic patients in Puskesmas Krian Sidoarjo in March-April 2015. Respondents were only 16 and had been divided into experiment and control group. The independent variable was the implementation of HAPA. The dependent variable were self-efficacy, dietary adherence and blood sugar levels. The instruments in this study were questionnaires and blood sugar monitoring devices. Data were analyzed using statistical wilcoxon sign rank test and mann whitney u test with significance level α ≤ 0.05.Result: Wilcoxon sign rank test showed there were differences between pre and post test significantly on self-efficacy (p=0.014), dietary adherence (p=0.025), blood sugar levels (p=0.009) in experiment group, while no significant differences in control group. Mann Witney U test showed that there was significant difference on dietary adherence (p=0.002) between two groups.Discussion: In conclusion, the implementation of HAPA can improve dietary adherence in type 2 diabetic patient. Further, following studies are expected with large number respondents and identify the whole variables in the HAPA theory.